2w+4x+12y+7w+10x-4w=

Simple and best practice solution for 2w+4x+12y+7w+10x-4w= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2w+4x+12y+7w+10x-4w= equation:


Simplifying
2w + 4x + 12y + 7w + 10x + -4w = 0

Reorder the terms:
2w + 7w + -4w + 4x + 10x + 12y = 0

Combine like terms: 2w + 7w = 9w
9w + -4w + 4x + 10x + 12y = 0

Combine like terms: 9w + -4w = 5w
5w + 4x + 10x + 12y = 0

Combine like terms: 4x + 10x = 14x
5w + 14x + 12y = 0

Solving
5w + 14x + 12y = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-14x' to each side of the equation.
5w + 14x + -14x + 12y = 0 + -14x

Combine like terms: 14x + -14x = 0
5w + 0 + 12y = 0 + -14x
5w + 12y = 0 + -14x
Remove the zero:
5w + 12y = -14x

Add '-12y' to each side of the equation.
5w + 12y + -12y = -14x + -12y

Combine like terms: 12y + -12y = 0
5w + 0 = -14x + -12y
5w = -14x + -12y

Divide each side by '5'.
w = -2.8x + -2.4y

Simplifying
w = -2.8x + -2.4y

See similar equations:

| 3m(7-21m)=0 | | 7x-y+49=0 | | 5(x+5)+5=5(x-8) | | 6x+8=4x-8 | | -22x-114-3x=-44x | | 9/2+49/4+7/2+3/4= | | -7(w-2)=5(3-3) | | -0.8(w-8)=0.4(3w-9) | | 4(x+4)-8x=4 | | N+2n+5+5=4(n+4) | | T=.65(39.153)+5.83 | | 5s^2+7s+2=0 | | 2(x+3)-12=4x+2 | | 7x^2+77x+x+11=171 | | x+11.6=-5.4 | | 89-5x-7=14x+1 | | (2)+(-8)+(10)= | | 7.6s=31.92 | | -2(v+1)+5v=2(v+1)-2 | | 7v^2-126=21v | | 2x=5.4 | | 7w-46=-2(w-4) | | (2)+(8)= | | 7x+13x-3+8x+15=180 | | (-2)+(8)= | | (-0.10)(11)+(0.45x)=0.05(x-6) | | -2(v+1)-3v=2(v-6) | | (-8)+(-2)= | | 2x-2+8=5x-6 | | 24x^2+25x-47=0 | | x^2+7-108=0 | | -2(v+1)-3u=2(u-6) |

Equations solver categories